Ameliorating Effects of SaturejaedmondiBriq Essential Oil on Reproductive Parameters in Pentylenetetrazol Induced Epilepsy Model in Adult Male Rats - Somayeh Bohlouli; Gelavij Mahmoodi (Fasa University of Medical Sciences, 2021)
Background & Objective: Epilepsy is a common neurological disorder that causes unpredictable, recurrent seizures. Increased oxidative stress plays an important role in the pathogenesis of epilepsy. Oxidative stress and epilepsy have negative effects on the reproductive system and cause infertility. Antioxidants are effective in reducing infertility disorders. SaturejaedmondiBriq is known as a powerful antioxidant that can reduce the effects of oxidative stress. The aim of this study was to evaluate the effects of Satureja edmondi on reproductive parameters in pentylenetetrazol (PTZ)-induced epileptic and normal male rats. Materials & Methods: A total of 48 Wistar adult male rats, with an average age of 10 weeks and a weight range of 240-260g, were used in this experimental study. Animals were randomized into normal and kindled groups that were treated with 150 and 300 ppm S. edmondi essential oil. Treatment of animals lasted 4 weeks. At the end of the study, the rats'testes were removed following anesthesia. The testes were weighed, and sperm parameters were measured according to the World Health Organization (WHO) standards. Data were analyzed by one‐way ANOVA test, and P<0.05 was considered statistically significant. Results: This study showed that sperm parameters, including sperm count, sperm viability, and progressive sperm motility significantly decreased in epileptic rats compared to normal rats (p≤.001). These parameters significantly increased at 150 and 300 ppm doses of S. edmondi essential oil in the Kindled groups) p≤.001 (. Sperm parameters significantly increased at 300 ppm dose of S. edmondi essential oil in normal groups (p≤.001). Moreover, changes in testis weight were not significant in the treatment groups. Conclusions: Satureja edmondi Briq, with abundant antioxidant compounds, improves the pathological changes induced by testicular oxidative stress in tic rats. S. edmondi as a good source of antioxidants can improve sperm parameters and reproductive potential in PTZ-induced epileptic male rats.